Poor Nutrition Status and Associated Feeding Practices among HIV-Positive Children in a Food Secure Region in Tanzania: A Call for Tailored Nutrition Training - Bruno Sunguya; Krishna C. Poudel; Linda B. Mlunde; David Urassa; Junko Yasuoka; Masamine Jimba (2014)
Undernutrition among HIV-positive children can be ameliorated if they are given adequate foods in the right frequency and diversity. Food insecurity is known to undermine such efforts, but even in food rich areas, people have undernutrition. As yet no study has examined feeding practices and their associations with nutrition status among as HIV-positive children in regions with high food production. We therefore examined the magnitude of undernutrition and its association with feeding practices among HIV-positive children in a high food production region in Tanzania. Methods We conducted this mixed-method study among 748 children aged 6 months-14 years attending 9 of a total of 32 care and treatment centers in Tanga region, Tanzania. We collected quantitative data using a standard questionnaire and qualitative data through seven focus group discussions (FGDs). Results HIV-positive children had high magnitudes of undernutrition. Stunting, underweight, wasting, and thinness were prevalent among 61.9%, 38.7%, 26.0%, and 21.1% of HIV-positive children, respectively. They also had poor feeding practices: 88.1% were fed at a frequency below the recommendations, and 62.3% had a low level of dietary diversity. Lower feeding frequency was associated with stunting (β = 0.11, p = 0.016); underweight (β = 0.12, p = 0.029); and thinness (β = 0.11, p = 0.026). Lower feeding frequency was associated with low wealth index (β = 0.06, p<0.001), food insecurity (β = −0.05, p<0.001), and caregiver's education. In the FGDs, participants discussed the causal relationships among the key associations; undernutrition was mainly due to low feeding frequency and dietary diversity. Such poor feeding practices resulted from poor nutrition knowledge, food insecurity, low income, and poverty. Conclusion Feeding practices and nutrition status were poor among HIV-positive children even in food rich areas. Improving feeding frequency may help to ameliorate undernutrition. To improve it, tailored interventions should target children of poor households, the food insecure, and caregivers who have received only a low level of education.